THE EFFECT OF NON-PHARMACOLOGICAL THERAPY ON PAIN REDUCTION IN POST OP FRACTURE PATIENTS - Saputri, Berlian Yuli; Ria Anggraini; Ketjuk Herminaju; Dwi Retnowati (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Fracture is a disruption of the continuity of bone tissue caused by traffic accidents or deformity. Fracture surgery is an invasive procedure that is usually performed on fracture patients. Surgery will of course have unpleasant impacts on the patient, one of which is pain. Pain arising from surgery or post-surgery can be reduced using non-pharmacological techniques. Non-pharmacological techniques that can be applied include deep breathing techniques, classical music therapy, cold compress therapy, aroma therapy, and finger-hold relaxation techniques. Objective: This research aims to analyze journals related to non-pharmacological techniques in reducing post-operative fracture pain. Method: Using literature review. The research samples analyzed were 5 articles. Data collection tools use Google Scholar, ResearchGate, and PubMed. Results: The 5 articles used in this literature review show an influence or reduction in the intensity of post-fracture surgery pain after being given non-pharmacological therapy. Conclusion: Non-pharmacological techniques can be used on patients who experience post-fracture surgery pain because the results of the analysis of several articles state that there is an influence or reduction in the intensity of post-fracture surgery pain.